Galectin-9 contributes to the survival of fully allogeneic skin grafts by modulating effector T cells and Tregs imbalance: Treatment for survival of allogeneic skin grafts - Luo, Yu; Shi, Bingyi; Qian, Yeyong; Bai, Hongwei; Liu, Feng (Cellular and Molecular Biology, 2023)
Allogeneic skin transplantation is an important clinical treatment for many diseases. Although Galectin-9 demonstrates multifaceted roles in modulating immune cell homeostasis and inflammation, its precise impact on balancing effector T cells and Tregs during allogeneic skin transplantation remains uncertain. This work was performed to evaluate the modulation of the survival time of allogeneic skin grafts by Gal-9 and to explore the critical mechanism involved in this process. Skin graft transplantation was conducted using C57BL/6 and BALB/c mice. Additionally, the levels of IL-2, IFN-γ, IL-4, and IL-17A were measured. Hematoxylin and eosin staining assay was performed to analyze the pathological conditions of skin grafts of experiment mice. The results revealed that Gal-9 noticeably prolonged the survival of the allogeneic skin graft and ameliorated the damage caused by acute immune rejection. Furthermore, Gal-9 resulted in selective reduction of effectors T cells such as Th1, and Th17. Simultaneously, Gal-9 didn’t attenuate the protective function for allograft, which alleviated the immune rejection caused by abnormal immune imbalance. Gal-9 exhibited a therapeutic effect on the allogeneic skin graft by selectively reducing CD4+TIM-3+ T effector cells and inducing a shift from a Th1 to an anti-inflammatory Th2 response. Furthermore, Gal-9 did not attenuate the protective function. Our present study may represent a novel therapeutic candidate for modulating effector T cells and Tregs imbalance-based therapy of allograft transplantation.